Development of a high-spatial-resolution annual emission inventory of greenhouse gases from open straw burning in Northeast China from 2001 to 2020 - Z. Song; Z. Song; L. Zhang; C. Tian; Q. Fu; Q. Fu; Z. Shen; R. Zhang; D. Liu; D. Liu; S. Cui; S. Cui (Atmospheric Chemistry and Physics)
Open straw burning has been widely recognized as a significant source of greenhouse gases (GHGs), posing critical risks to atmospheric integrity and potentially exacerbating global warming. In this study, we proposed a novel method that integrates crop cycle information into extraction and classification of fire spots from open straw burning in Northeast China from 2001 to 2020. By synergizing the extracted fire spots with the modified fire radiative power (FRP) algorithm, we developed high-spatial-resolution emission inventories of GHGs, including carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O). Results showed that the northern Sanjiang Plain, eastern Songnen Plain, and eastern Liao River plain were areas with high intensity of open straw burning. The number of fire spots was evaluated during 2013–2017, accounting for 58.2 % of the total fire spots observed during 2001–2020. The prevalent season for open straw burning shifted from autumn (pre-2016) to spring (post-2016), accompanied by a more dispersed pattern in burning dates. The 2-decade cumulative emissions of CO2, CH4, and N2O were quantified at 198 Tg, 557 Gg, and 15.7 Gg, respectively, amounting to 218 Tg of CO2-eq (equivalent). Significant correlations were identified between GHG emissions and both straw yield and straw utilization (p<0.01). The enforcement of straw-burning bans since 2018 has played a pivotal role in curbing open straw burning and has reduced fire spots by 51.7 % on an annual basis compared to 2013–2017. The novel method proposed in this study considerably enhanced the accuracy in characterizing spatiotemporal distributions of fire spots from open straw burning and quantifying associated pollutant emissions.